2010
DOI: 10.1039/b926391h
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-induced electrostatic etching: generation of highly reactive magnesium for application in Grignard reagent formation

Abstract: A detailed study regarding the influence of microwave irradiation on the formation of a series of Grignard reagents in terms of rates and selectivities has revealed that these heterogeneous reactions may display a beneficial microwave effect. The interaction between microwaves and magnesium turnings generates violent electrostatic discharges. These discharges on magnesium lead to melting of the magnesium surface, thus generating highly active magnesium particles. As compared to conventional operation the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…[17] The instrument uses a maximum of 850 W magnetron output power (2.45 GHz) and can be operated at 300 8C reaction temperature and 30 bar pressure. The reaction temperature was monitored by an external infrared sensor (IR) housed in the side-walls of the microwave cavity measuring the surface temperature of the reaction vessel, and/or by an internal fiber-optic (FO) temperature probe (ruby thermometer) [42] protected by a borosilicate immersion well inserted directly to the reaction mixture. The magnetron output power can either be controlled by the FO probe (IR as slave) or by the IR sensor (FO as slave).…”
Section: Microwave Irradiation Experimentsmentioning
confidence: 99%
“…[17] The instrument uses a maximum of 850 W magnetron output power (2.45 GHz) and can be operated at 300 8C reaction temperature and 30 bar pressure. The reaction temperature was monitored by an external infrared sensor (IR) housed in the side-walls of the microwave cavity measuring the surface temperature of the reaction vessel, and/or by an internal fiber-optic (FO) temperature probe (ruby thermometer) [42] protected by a borosilicate immersion well inserted directly to the reaction mixture. The magnetron output power can either be controlled by the FO probe (IR as slave) or by the IR sensor (FO as slave).…”
Section: Microwave Irradiation Experimentsmentioning
confidence: 99%
“…[9] The authors demonstrated that for certain substrates (e.g. 2-halothiophenes) the formation of the corresponding organomagnesium reagents could be significantly accelerated by applying microwave irradiation at constant power utilizing a multimode instrument.…”
mentioning
confidence: 99%
“…[9] To perform valid comparative studies of arcing results achieved in individual single-mode microwave reactors, experiments under sealed vessel conditions were subsequently carried out in the Discover system. A stirred Mg/ THF mixture exposed to 300 W of constant microwave power in a 10 mL sealed pyrex vial reached a temperature of 65 8C, corresponding to the boiling point of THF, within 17 s. After this comparatively short irradiation period, the Mg turnings appeared essentially unchanged (Figure 2 a).…”
mentioning
confidence: 99%
“…A recent study on Grignard reagent formation argued that such violent discharges lead to the melting of the magnesium surface, thereby generating highly active metal particles [69]. Under these circumstances, it is also convenient to work under vacuum to reduce the risk of spontaneous ignition of the pyrophoric material.…”
Section: Microwave-and Ultrasound-enhanced Synthesis and Catalysismentioning
confidence: 99%